The early years curriculum : a view from outdoors - Callaway, Gloria (David Fulton, 2005)
Based on an account of Cornwall's Education Action Zone project, this book explores how to plan, implement and assess a rigorous outdoor early years curriculum that complements classroom-based learning and meets the Early Learning Goals.